Zika virus noncoding RNA suppresses apoptosis and is required for virus transmission by mosquitoes - Andrii Slonchak (Nature Portfolio, 2020)
The function on subgenomic flaviviral RNA (sfRNA) in the mosquito vector is not well understood. Here, Slonchak et al. show that sfRNA affects virus-induced apoptosis and dissemination of ZIKV in Aedes aegypti mosquitoes, suggesting a role of sfRNA in Zika virus replication and transmission.